RACIAL STEREOTYPES TOWARD JEWISH IN “FAMILY GOY” EPISODE OF “FAMILY GUY” - KURNIAWAN, RYAN PRAWIRA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keyword: Ethnorace, Racial Stereotype, Family Goy, Jewish.People or society is not distant from stereotype attached to them. Jewish, one of the ethnorace, also has certain stereotypes. Religion has a lot of characteristics from their information with stereotypes. Stereotype is how people overgeneralize information about another group.“Family Guy” as a television series in America reflects social values of the people, including Jewish. Especially in episode entitled “Family Goy”, Jewish are depicted as to have some stereotypes. Therefore, this problem of this study is to reveal racial stereotype as depicted in “Family Goy” episode of “Family Guy”.In “Family Goy”, Jews are stereotyped as money minded, devoted to god, survivors, tidy, and hairy. These categories are based on unique and religious characteristics of Jew which are depicted in the series of Family Guy“Family Goy” episode of “Family Guy” shows stereotypes labeled to Jewish group as reflected in every scene of the series “Family Goy” episode of “Family Guy”.